Pediatric magnetoencephalography - Douglas R. Nordli III; Fernando N. Galan (Annals of the Child Neurology Society)
Abstract Magnetoencephalography (MEG) is a technology used in pediatric and adult epilepsy that records magnetic fields produced from electric currents in the brain. MEG can locate epileptogenic zone(s), lateralize language functions, localize sensorimotor cortex, and identify visually evoked fields. It is a powerful technology with key advantages in pediatrics. The majority of its limitations are resource driven. With advancing technology, MEG will become a more prominent and valuable tool used in pediatric epilepsy and epilepsy surgery in the future. We review MEG and provide illustrative cases to showcase its usage.